Specifications of Free Verse Writing in Lesja Ukrajinka’s Heritage - Naumenko, Nataliia (My University, 2021)
The article gives an analysis of several poems taken from Lesja Ukrajinka’s nature philosophical verses written in the free form. What became the initials for this research was the nature of free verse, which would allow determining the specifications of generic and stylistic diffusion in works of a certain poet and observe formation of an individual vision of the world, thereby reflected in re-interpreted initials of folklore verse. The objectives of this work are to establish the formal and substantial features of free verse writing in the poetic works by Lesja Ukrajinka upon studying three most famous free verses (“Fragments from the Letter,” “Ave Regina!”, and “Spring in Winter”). Concisely, there was concluded that the formal and substantial conceits of Lesja’s creativity, the choice of genre and versification order first, evidence her endeavor to return to initial artistic syncretism. Particularly, her free verse, upon combining the prosodic systems dominant in Modernist literary process in Ukraine, appears to be the successor of preliminary versification traditions (folk duma verse) and, at the same time, the founder of those new. It is the factor that defines the special imagery of free verse works, including various lexical massifs (exotic, colloquial, or dialect words), artistic and scientific terms, and composition of a verse as a narration with profound philosophical content.
Keywords: кафедра іноземних мов професійного спрямування; поезія Лесі Українки; вільний вірш; метрика; образ; poetry by Lesja Ukrajinka; free verse; metrics; image